Species Distribution Modelling Of Treeshrew (Genus Tupaia) In Malaysian Borneo - Lydia Natasha, Yeo (Universiti Malaysia Sarawak (UNIMAS), 2022)
Treeshrew of the genus Tupaia (Order Scandentia, Family Tupaiidae) is widely spread throughout Borneo and most member of this genus are listed as Least Concern in the IUCN Red List. However, its species distribution modelling in Malaysian Borneo is still lacking in providing information on the possible future distribution and habitat suitability. This study aims to map the distribution based on secondary data and to identify the best environmental variable that may influence the distribution of the species in genus Tupaia in Malaysian Borneo. A total 101 presence points of treeshrew from Malaysian Borneo were collected and compiled from various examined sources such as journals, publication papers, research studies, websites open access and museum specimens of UNIMAS Zoological Museum. Nineteen bioclimatic variables and elevation data were downloaded from the WorldClim database. Both presence points and environmental layers were run into Maximum Entropy software and seven predicted distribution models of treeshrew were presented. The best environmental variable that influenced the distribution of treeshrew is Bio 4 (T. dorsalis), Bio 12 (T. longipes), Bio 13 (T. minor and T. tana), Elevation (T. montana), Bio 16 (T. picta) and Bio 18 (T. gracilis). Thus, species distribution modelling is vital to predict the distribution and habitat suitability of treeshrew to plan conservation measure especially conservation of lowland, hills, and montane tropical forests as well as protected areas to help in ensuring their survivability in the wild. Hopefully there will be more sampling effort be done to cover the unsampled area on treeshrews in Malaysian Borneo.